Review of the psychometric properties of the Patient Health Questionnaire-9 (PHQ-9) Spanish version in a sample of Puerto Rican workers - Rosario-Hernández, Ernesto; Rovira-Millán, Lillian V.; Merino-Soto, César; Angulo-Ramos, Marisol (Frontiers in Psychiatry, 2023)
Background: The aim of the current study was to examine the internal structure and assess the psychometric properties of the Patient Healthcare Questionnaire (PHQ-9) in a Puerto Rican sample of workers. This instrument is a nine-item questionnaire, which was conceptualized as unidimensional structure; however, there are mixed results regarding this internal structure. This measure is used in the occupational health psychology context in organizations of Puerto Rico; nevertheless, there is little evidence of its psychometric properties with samples of workers. Materials and Methods: A total sample of 955 from two different study samples was used in this cross-sectional study design in which the PHQ-9 was used. We conducted confirmatory factor analysis, bifactor analysis and random intercept item factor analysis to examine the internal structure of the PHQ-9. Moreover, it was examined a two-factor model randomly assigning items to the two factors. Measurement invariance across sex and the relationship with other constructs were examined. Results: The best fitted model was the bifactor model followed by the random intercept item factor. The five sets of two-factor models with items randomly assigned obtained acceptable and similar fit indices regardless the items. Conclusion: The results suggest that the PHQ-9 appears to be a reliable and valid instrument to measure depression. The more parsimonious interpretation of its scores, for now, is a unidimensional structure. Comparison across sex appear to be useful in occupational health psychology research setting since results suggest that the PHQ-9 is invariant regarding this variable.